Campur kode dalam pembelajaran Keterampilan Membaca [kajian analisis deskriptif di IAIN IB Padang] - Jaka Imam Mahesa (Taqdir, 2020)
The purpose of this study is: (1) knowing the mixed forms of code in reading learning, (2) knowing why the code mixing was used, (3) knowing the underlying contribution of reading learning. The research approach used is the qualitative analyce-descriptive approach, the research data collection technique is observation and documentation, using miles and huberman data analysis, that is, data reduction, data presentation and deduction. Research indicates that the mixing code used by the professor was elements of sentences (1) words and phrases, (2) sounds, (3) vocabulary, (4) grammar. Kind of mixing code, internal code mixing. As for the emergence of code mixing, (1) at least certain terms in Indonesian or Arabic cannot be translated, (2) academic purposes and reasons, (3) drawing attention from a speech partner. The corresponding contribution of code mixing in reading learning (1) explains I 'rab, (2) explains the meaning of a vocabulary, (3) develops a vocabulary. Keywords: Code Mixing, Learning, Qira’ah